The emergence and development of behavioral individuality in clonal fish - Laskowski, Kate L.; Bierbach, David; Jolles, Jolle W.; Doran, Carolina; Wolf, Max (Nature communications, 2022)
Behavioral individuality is a ubiquitous phenomenon in animal populations, yet the origins and developmental trajectories of individuality, especially very early in life, are still a black box. Using a high-resolution tracking system, we mapped the behavioral trajectories of genetically identical fish ( Poecilia formosa ), separated immediately after birth into identical environments, over the first 10 weeks of their life at 3 s resolution. We find that (i) strong behavioral individuality is present at the very first day after birth, (ii) behavioral differences at day 1 of life predict behavior up to at least 10 weeks later, and (iii) patterns of individuality strengthen gradually over developmental time. Our results establish a null model for how behavioral individuality can develop in the absence of genetic and environmental variation and provide experimental evidence that later-in-life individuality can be strongly shaped by factors pre-dating birth like maternal provisioning, epigenetics and pre-birth developmental stochasticity. You’re unique just like everyone else. But when does such individuality appear? Laskowski et al. find that clonal fish show unique behavioral patterns on their first day of life, and these patterns predict their behavior up to at least 10 weeks later.